2019
DOI: 10.1093/annonc/mdz051
|View full text |Cite
|
Sign up to set email alerts
|

European cancer mortality predictions for the year 2019 with focus on breast cancer

Abstract: Background: To overcome the lag with which cancer statistics become available, we predicted numbers of deaths and rates from all cancers and selected cancer sites for 2019 in the European Union (EU). Materials and methods: We retrieved cancer death certifications and population data from the World Health Organization and Eurostat databases for 1970-2014. We obtained estimates for 2019 with a linear regression on number of deaths over the most recent trend period identified by a logarithmic Poisson joinpoint re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
127
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(145 citation statements)
references
References 34 publications
2
127
0
6
Order By: Relevance
“…We only mentioned in two lines a possible role of decrease in menopausal hormone use on national breast cancer rates [2]. Indeed, changes in hormonal replacement therapy (HRT) use had a relevant impact on incidence, but their influence on mortality is limited and not adequately quantified [3,4].…”
Section: And Hamoda On Behalf Of the British Menopause Society Medicmentioning
confidence: 99%
See 1 more Smart Citation
“…We only mentioned in two lines a possible role of decrease in menopausal hormone use on national breast cancer rates [2]. Indeed, changes in hormonal replacement therapy (HRT) use had a relevant impact on incidence, but their influence on mortality is limited and not adequately quantified [3,4].…”
Section: And Hamoda On Behalf Of the British Menopause Society Medicmentioning
confidence: 99%
“…Local recurrence and survival after treatment are highly related to the degree of extramural spread within the T3 category with a heterogeneity far greater than for any other T stage, with local recurrence ranging from less than 10% to over 20%. Histopathological analysis of cancer-specific end points within the T3 category has shown that its division into pT3a and pT3b subgroups in which extramural spread is up to and including 5 mm in the former and more than 5 mm in the latter is the strongest locoregional prognostic factor of local recurrence and survival [1][2][3]. Staging pretreatment MRI now forms the basis for management planning for locoregional disease, including the decision to recommend chemoradiation and the subsequent assessment of tumour response when this is given.…”
Section: Extramural Spread Of Rectal Cancer and The Ajcc Cancer Stagimentioning
confidence: 99%
“…As for pathological discrimination, 70% are nonsquamous, ie, adeno‐ or large cell carcinomas . In the Europe‐wide estimation for 2019, NSCLC will account for 23% and 15% of all cancer deaths in men and women, respectively . According to the eighth edition of the TNM classification stage III NSCLC summarizes a scope of diverse subentities.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is prevalent in 12% of women in the USA more than 2.5 million new cases of breast cancer were diagnosed in 2017 [19]. The rate for breast cancer declined by 35% in last 3 decades but number of deaths remains same [20]. The 3 most prevalent cancers in 2019 are prostate, colorectal and skin melanoma among males, and breast, uterine corpus, and colorectal among females [21].…”
Section: Introductionmentioning
confidence: 99%